Fenomena Penggunaan Bahasa Slang dalam Budaya K-Pop dan Pengaruhnya terhadap Gaya Hidup serta Identitas Generasi Muda - Naila Kinanti; Eryne Adelia; Khairunnisah Tanjung (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study examines the phenomenon of K-Pop slang usage among young generations and its influence on lifestyle and social identity formation. The research background reveals that K-Pop culture has significantly impacted language practices, particularly through the adoption of specific terms within fan communities. The objective is to analyze how K-Pop slang functions as a linguistic creativity tool and identity marker among Indonesian youth. Using a qualitative descriptive approach, data were collected from social media platform X (Twitter) through purposive sampling of posts containing K-Pop slang terms. Findings indicate that K-Pop slang encompasses semantic shifts, acronyms, abbreviations, and new terminology that strengthen community solidarity and collective identity. The implications suggest that while K-Pop slang serves as creative expression and social bonding mechanism, excessive usage may affect proper Indonesian language proficiency in academic contexts. This research contributes to understanding the balance between linguistic creativity, global cultural influence, and Indonesian language preservation.